Ethical Implications of Usage of AI Models by Undergraduate Students in Academia - Do, Tuan (2024)
This thesis aims to discuss and elaborate the ethical concerns that are brought to light in the use of artificial intelligence (AI) among undergraduate college students. This is presented through the description and analysis of decision-making processes and various ethical dilemmas that undergraduates regularly face while using AI models to assist with their academic work. AI refers to digital technologies or automated machines that can simulate diverse aspects of human intellect. Conversely, in an educational context, students use AI tools to serve various functions, such as writing, paraphrasing, and summarizing content. The most commonly used AI tools include generative AI tools, of which ChatGPT is the most popular and widely used tool by students for academic help. Even though these tools save much of the students' time and are convenient, their use comes with a variety of ethical dilemmas, such as infringing on academic integrity and honesty. To investigate these ethical implications, this thesis deployed a mixed-methods study. The study included a secondary qualitative case analysis of four case studies on AI usage in academia. These case studies were supplemented by a primary quantitative public survey that polled 58 participants (including 34 undergraduate exchange students) in the Czech Republic. The survey sought responses from the respondents concerning their use of AI tools and their awareness of the ethical consequences associated with their usage. The four case studies establish that AI usage is rampant among students as well as faculty, and this usage has been on an upward trend with the surge in the number of AI tools available online. The case studies also affirm that institutions are aware of student use of AI tools and have taken proactive policy steps to promote ethical and responsible use.